Neonatal Surgery Intensive Care Unit: Hacettepe University Experience - Umit Ayse Tandircioglu; Hasan Tolga Celik; Sule Yigit; Murat Yurdakok (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: Surgical treatment in the neonatal period is very significant. The neonatal surgery intensive care model has been applied in our hospital for about six years. This study aims to examine the data gathered from the neonatal intensive care unit of our hospital and to understand how this model contributed to the health improvement of newborns with surgical problems.